Структурно-стильові та графічні особливості релігійних абеток і букварів - Тарасюк, Тетяна; Tarasiuk, Tetiana (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті проаналізовано структурно-стильові та графічні особливості сучасних релігійних абеток і букварів. Розглянуто визначення лексем абетка, азбука, алфавіт, буквар за лексикографічними джерелами та встановлено їх дефініції. З’ясовано будову словникової статті реєстрових літер у досліджуваних джерелах, її лексичне наповнення та графічне увиразнення. The article attempts to analyze structural, stylistic and graphic peculiarities of modern religious ABC-books and primers. The author provides definitions of the lexemes ABC, alphabet, ABC-books, primer, compiled on the basis of the variants represented in the lexicographical sources. The emphasis is laid on the genre specifics of textbooks, which are designed not only to teach a child to read, but also to introduce him to the world of native language, and religious ABC-books also lay the foundations of Christian morality. Analysis of the structural organization of primers gives reason to believe that «Bukvaryk-vocabulary» concisely combines the features of the alphabet, vocabulary and primer, and «Orthodox primer» tends to media type that has features of the books for reading in the family. The article reports and discusses the structure of the dictionary entry of register letters in the sources under the analysis and concludes that it depends greatly on the genre of educational literature (ABC Book or Primer) and its lexical and graphic content. The perspective of further study of the problem implies comparison of architectonics of religious and secular hornbooks or primers.
Structural, Stylistic and Graphic Peculiarities of the Religious ABC-books and Primers
Keywords: абетка; азбука; алфавіт; буквар; словникова стаття; реєстрова літера; ілюстрації; hornbook; ABC-book; alphabet; primer; dictionary entry; a register letter; illustration